Pemberdayaan Masyarakat Pada Perayaan Gebyar Ramadhan 1442 H/2022 M Untuk Pengembangan Nilai-Nilai Keislaman Remaja - Mumu Muzayyin Maq (Jurnal Pengabdian Masyarakat Bestari, 2022)
Empowerment is a process of giving power, strength to individuals or groups to achieve a certain goal. The purpose of this activity provides services and assistance to the community in formation of Islamic values. This activity is carried out in April –May 2022 in Pekauman RT. 03 RW  01 Leuwimunding, Majalengka Regency. The activity include taraweh, small speech (kultum), riciting the holy Qur’an, evening prayers and traveling activities to wake up sahur. The method used in this activity is Participatory Action Research (PAR). The results obtained from activity are added value to the formation of Islamic values ​​in adolescents and the local community. The implications of this are  appreciation, active role and participation in all activities that have been scheduled.